Theatrical Prosthesis – Widening Horizons of Prosthetic Dentistry – A Case Report (Indian Journal of Forensic Medicine & Toxicology, 2020)
A movie or a play is said to be great if it can imprint an image in our mind forever. To accomplish this, eventhe unnatural looking characters should look real. This case report describes a temporary prosthesis whichalters the look of a theatre artist suited as a Dracula. Mock wax-up was done on the stone cast and an indexof same was made using putty material. After dewaxingof the cast, tooth colored self-cure acrylic resin wasmixed and poured into the index and stone cast with separating medium applied over it was pressed into theindex. Prosthesis was retrieved, trimmed, polished and then delivered to patient.